Analisis Efektivitas Implementasi Kebijakan Subsidi Pupuk Terhadap Tingkat Penggunaan Pupuk Petani Padi di Desa Curug Kabupaten Karawang - Devianti, Yulianissa; Abubakar, Abubakar; Yusiana, Ekalia (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2024)
Fertilizer subsidy policy is one of the fiscal policies that aims to support the agricultural sector by providing input subsidies in the form of setting HET for fertilizer. This policy is implemented based on six indicators of success, namely the right type, quantity, price, quality, place, and time. This study aims to analyze the effectiveness of the fertilizer subsidy policy based on six precise indicators that determine the success of fertilizer subsidies and to analyze the relationship between the effectiveness of the fertilizer subsidy policy and the level of fertilizer use. The technique used to identify respondents in this study was purposive sampling. The number of samples used were 30 respondents. Test instruments in this study used validity and reliability tests while the relationship between effectiveness and the level of fertilizer use was analyzed using the Rank Spearmen Correlation test. The results showed that the fertilizer subsidy policy that was implemented in Curug Village, Klari District, Karawang Regency was quite effective. The results of the analysis of the relationship between the effectiveness of the fertilizer subsidy policy and the level of fertilizer use do not have a positive correlation (correlation) with a correlation coefficient of 0.316 which is included in the weak category.